The Role of Work Passion and Work Engagement in Improving Teacher Well-Being in High School - Nugroho, Muhammad Ghifari; Harahap , Farida (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Teacher well-being has become the focus of contemporary educational research in response to the increasing phenomenon of work stress, burnout, and psychological pressure on educators. Previous studies have indicated that teachers are significantly more susceptible to emotional exhaustion and decreased job satisfaction than other professions, which have implications for the quality of learning and student academic achievement. This study aims to analyze the effect of work passion and work engagement on teacher well-being in high school teachers in Pringsewu Regency. This study uses a quantitative approach with a survey method on 255 ASN teachers from seven state high schools in Pringsewu Regency, Lampung. Data collection was conducted from February to March 2025 using three instruments: The Work Passion Scale, Work Engagement Scale, and Teacher Well-Being Scale. The sampling technique used is purposive sampling. Data analysis uses multiple linear regression to test the effect of independent variables on the dependent variable. The results of the study indicate that work passion and work engagement simultaneously have a significant effect on teacher well-being. Based on these findings, it is recommended that educational institutions develop programs that promote harmonious passion and work engagement, as well as facilitate a work environment that supports a healthy work-life balance to improve teacher well-being.